Democracy and Economic Welfare: An Empirical Analysis - Afrimadona Afrimadona; Shanti Darmastuti; Laode Muhamad Fathun (Journal of Governance, 2019)
This article assesses the relationship between democracy and welfare policy. There are substantial variations in the empirical evidence regarding the relationship between these two variables. While some works showed that there is a systematic relationship between democracy and welfare policy, others failed to show that relationship. We argue that we need to look at the internal political variables within these democracies in order to see what factors within those polities that can lead to a more welfare-oriented policy. We further argue that democracies with parliamentary system and proportional representation are more likely to adopt welfare-oriented policy. Using panel data of 32 democracies from 1961 to 2015, we find some empirical supports for our argument.